Quiste mesotelial gigante - Ramos Torres, Guillermo (2025)
In the differential diagnosis of peritoneal masses, in addition to metastatic disease, primary tumors such as simple mesothelial cysts should be considered. We present the case of a 44-year-old man with progressive abdominal distension, initially suggestive of cirrhosis with ascites. However, the physical exam revealed no stigmata of chronic liver disease. Abdominal computed tomography revealed a cystic lesion. Laparotomy and cystectomy were performed, identifying an intra-abdominal cyst measuring 40 × 30 × 30 cm. Histopathological analysis confirmed a benign mesothelial cyst. Simple mesothelial cysts are usually asymptomatic until they reach a large size, causing nonspecific symptoms. Computed tomography and magnetic resonance imaging are key tools for their diagnosis. In symptomatic cases or those with associated complications, complete surgical excision is the treatment of choice, as it reduces recurrence and allows for diagnostic confirmation.